Evaluation of cowpea (Vigna unguiculata (L.) Walp.) landraces to bacterial blight caused by Xanthomonas axonopodis pv. vignicola - Durojaye, H.A.; Moukoumbi, Y.D.; Dania, V.O.; Boukar, O.; Bandyopadhyay, Ranajit; Ortega Beltran, A. (Elsevier, 2019)
Cowpea is an important protein source for human populations in many nations across sub-Saharan Africa (SSA). However, cowpea production is constrained by bacterial blight (CoBB) caused by Xanthomonas axonopodis pv. vignicola (Xav), a disease affecting most cowpea-growing areas. A large proportion of smallholder farmers across SSA rely on traditional cowpea landraces (CLR) to produce the crop. The International Institute of Tropical Agriculture (IITA) possesses the largest collection of cowpea germplasm, including several CLR accessions. However, screening for resistance to CoBB in most of the CLR accessions maintained at IITA has not been conducted. CoBB severity was evaluated in 103 CLR accessions from five African countries, the US, The Philippines, and Sri Lanka by artificially inoculating a highly virulent Xav strain in plants grown in a screenhouse. Highly significant (P < 0.0001) differences in susceptibilities to the disease were detected among the evaluated germplasm. Resistance was detected in several CLR accessions with two accessions from Nigeria and one from the US developing no disease symptoms. Our results indicate that several CLR accessions are valuable sources of resistance to CoBB and those could be used to breed for improved varieties with superior resistance to the disease. The resistant CLR accessions and others in IITA collection should be further investigated to identify additional beneficial traits that may contribute to the development of improved, commercially acceptable varieties.